EVALUATING THE IMPACT OF A TRAINING WORKSHOP ON PRESCRIPTION WRITING SKILLS: A PRE AND POST INTERVENTIONAL STUDY - Ubaidullah,; Mehboob, Usman; Adeeb, Humera; Raiz, Samreen (Journal of Ayub Medical College Abbottabad, 2025)
Evaluating the Impact of a Training Workshop on Prescription Writing Skills: A Pre and Post Interventional Study